Seasonal and regional structuring of rhizosphere fungal communities in Macadamia integrifolia - Ning, Ya; Chen, Yuchun; Wu, Zhonghua; Yang, Tingmei; He, Xiyong; Yue, Hai (Frontiers in Microbiology, 2025)
IntroductionRhizosphere fungal communities are pivotal to plant nutrient acquisition, stress tolerance, and ecosystem functionality. However, the diversity and ecological roles of these communities in tropical cash crops like Macadamia integrifolia (macadamia) remain understudied—particularly how they respond to seasonal, geographic, and root-type variations. This knowledge gap hinders targeted management of rhizosphere microbes for sustainable macadamia production.MethodsTo address this, we examined the spatiotemporal structuring of rhizosphere fungal communities in M. integrifolia across four major production regions in Yunnan Province, China (Changning, Yingjiang, Lancang, Yunxian). We accounted for three key variables: season (dry season: November–April; rainy season: May–October), root type (normal roots vs. cluster roots), and geography. A total of 80 soil samples were collected (4 regions × 2 seasons × 2 root types × 5 biological replicates). High-throughput sequencing of the fungal Internal Transcribed Spacer (ITS) region was used to analyze community composition, diversity, and functional guilds; co-occurrence network analysis and PERMANOVA were also employed to interpret community dynamics.ResultsSeason and geographic location significantly shaped fungal community structure, while the effect of root type was context-dependent. Fungal diversity was higher in the rainy season, with Ascomycota (55–65%), Basidiomycota (20–30%), and Mortierellomycota (5–10%) as the dominant phyla. Cluster roots enriched symbiotic and beneficial taxa: Glomus and Trichoderma were 1.8- and 2.3-fold more abundant in cluster roots than in normal roots, respectively. PERMANOVA confirmed significant effects of season and region on community structure (p = 0.001). Co-occurrence networks showed seasonal shifts in core taxa: dry-season networks were dominated by Talaromyces and Penicillium (Ascomycota), while rainy-season networks featured Cladosporium (Ascomycota) and Mortierellaceae (Mortierellomycota)—with 35% of edges being negative interactions in the rainy season, indicating heightened resource competition. FUNGuild predictions revealed saprotrophic fungi were predominant (50–55%), with a 10% higher proportion in rainy-season samples than in dry-season samples.DiscussionThis study clarifies the dynamic and region-specific nature of M. integrifolia rhizosphere fungal communities, highlighting how environmental factors drive their composition and function. These findings fill a critical knowledge gap and provide a foundational framework for future research on rhizosphere fungi in macadamia cultivation, supporting efforts to improve crop sustainability.